Technical Communication for Environmental Action - Williams, Sean D. (2023)
Climate change is one of the most significant challenges facing the global community in the twenty-first century. With its position at the border of people, technology, science, and communication, technical communication has a significant role to play in helping to solve these complex environmental problems. This collection of essays engages scholars and practitioners in a conversation about how the field has contributed to pragmatic and democratic action to address climate change. Compared to most prior work-which offers theoretical perspectives of environmental communication-this collection explores the actual practice of international technical communicators who participate in government projects, corporate processes, nonprofit programs, and international agency work, demonstrating how technical communication theories such as participatory design, social justice, and ethics can help shape pragmatic environmental action.